Effects of a 12-week aerobic exercise programme on human immunodeficiency virus-associated neurocognitive disorder in Nigeria - Mshunqane, Nombeko (University of Pretoria, 2022)
Thesis (PhD (Physiotherapy))--University of Pretoria, 2021.